L'angle mort de la « laïcité ouverte » : les processus de navigation et négociations dans le vécu religieux au Canada. (March 2020) - Selby, Jennifer A; Beaman, Lori G; Barras, Amélie
Building on our critiques of the reasonable accommodation of religious minorities in Canada (see Selby et al., 2018a ; Beaman, 2017 ; Barras, 2016), this paper argues for attention to processes as intrinsic to everyday interactions of religiosity (following Tully, 1995, 2000 ; Van Quaquebeke et al., 2007). We contend that frameworks like Maclure and Taylor's (2010) on 'open' and 'closed' secularism are useful for nation state comparison, but ineffectively account for the power asymmetries lodged within everyday religiosity. Their model protects the status quo ; it does not call institutional values or procedures into question, erases the navigation that occurs before an 'accommodation' is requested, and entrenches conflict as reflective of the experiences of religious minorities. Based on interviews with 90 self-defined Muslims in two cities, we propose a model of navigation and negotiation to better capture how religious practices are contextual and embedded in power relations.